Kematangan Gonad Ikan Cempedik (Osteochilus spilurus) Pada Musim Kemarau Di Sungai Bumang, Pulau Bangka - Tiara Damayanti; Ardiansyah Kurniawan; Tiara Puspa Anjani; Ahmad Fahrul Syarif (Samakia : Jurnal Ilmu Perikanan, 2024)
The Cempedik fish, which is popular on Belitung Island, is often studied for its gonadal maturity during the rainy season. This seasonal focus aligns with the peak fishing period for the species. However, no studies have yet been conducted on this species during the dry season. This research aims to analyze the gonadal maturity level of Cempedik fish (Osteochilus spilurus) during the dry season. Fish samples were collected from the Bumang River in Kemuja Village, Bangka Regency. A total of 30 fish were randomly sampled using traditional bamboo traps. Sampling was conducted at the peak of the dry season in July 2024. The majority of the fish showed gonadal maturity levels ranging from stages 3 to 4 in both males and females. The findings indicate that Cempedik fish, previously known to reach gonadal maturity during the rainy season, also exhibit high maturation levels in the dry season. This suggests that the species may reproduce throughout the year, during both the dry and rainy seasons.